Numerical solution of the time dependent Ginzburg-Landau equations for mixed (d plus s)-wave superconductors - Goncalves, W. C. [UNESP]; Sardella, Edson [UNESP]; Becerra, V. F.; Milosevic, M. V.; Peeters, F. M. (American Institute of Physics (AIP), 2014)
The time-dependent Ginzburg-Landau formalism for (d + s)-wave superconductors and their representation using auxiliary fields is investigated. By using the link variable method, we then develop suitable discretization of these equations. Numerical simulations are carried out for a mesoscopic superconductor in a homogeneous perpendicular magnetic field which revealed peculiar vortex states. (C) 2014 AIP Publishing LLC.